Pengaruh Model Pembelajaran Self Directed Learning Terhadap Kemampuan Berpikir Kreatif Siswa Pada Mata Pelajaran Akidah Akhlak MTs Syarif Hidayatulloh Kemuning Kedamean Gresik - Rofikhoh; Barudin; Achmad Khusnan (Konsorsium Pengetahuan Innoscientia (KOPINNOS), 2026)
The teaching of Akidah Akhlak is ideally aimed not only at knowledge acquisition but also at fostering students’ creative thinking skills. However, in practice, learning is still dominated by conventional methods such as lectures and memorization, leading students to become passive and less able to explore ideas. This creates a gap between the ideal goals of Akidah Akhlak learning and classroom reality. This study aims to analyze the effect of the Self Directed Learning (SDL) model on the creative thinking skills of grade VIII students at MTs Syarif Hidayatulloh Kemuning Kedamean Gresik. The research employed an experimental method with a One Group Pretest-Posttest Design. The sample consisted of 24 purposively selected students of class VIII-A. Data were collected through observation, tests, questionnaires, and documentation, and analyzed using a paired sample t-test. The findings revealed a significant improvement in students’ creative thinking, with the average pretest score of 74.80 increasing to 89.38 in the posttest. Teacher activities scored an average of 84% (very good), while student activities improved from 60.4% (fair) to 76.0% (good). Students’ responses were highly positive, with 94% agreeing or strongly agreeing with SDL implementation. In conclusion, SDL is effective in enhancing students’ independence, creativity, and engagement in Akidah Akhlak learning.